Outbreaks of Mycoplasmosis and Histomoniasis in a Southern Brazilian Flock of Ornamental Birds - de Oliveira, Luiz Gustavo Schneider; Boabaid, Fabiana Marques; Lorenzett, Marina Paula; Rolim, Veronica; dos Santos, Helton Fernandes; Driemeier, David; Cruz, Cláudio Estêvão Farias (Acta Scientiae Veterinariae, 2017)
Background: Infectious diseases have expanded their host and geographic ranges, increasing impacts on both human and animal health. Mycoplasma gallisepticum usually causes avian chronic respiratory conditions and Histomonas meleagridis infects the cecum and the liver of poultry. Although these diseases have been reported in several bird species, information associated with their prevalence and impact in local flocks of ornamental birds is scarce. This communication describes severe outbreaks of mycoplasmosis and histomoniasis that affected a southern Brazilian commercial flock of ornamental birds. Case: The outbreaks occurred in an ornamental bird flock that contained 2,340 birds from 39 different species, distributed mostly in the orders Galliformes, Anseriformes, and Psittaciformes. Mycoplasma gallisepticum affected 12 chukar partridges, 12 Indian peacocks, 19 ornamental chickens and 46 individuals of 4 species of pheasant. The disease cases were distributed between April and July 2015. A total of 36 birds died due to the disease’ complications and most surviving birds suffered from severe ocular sequels, which determined their subsequent culling, despite attempts of different treatment protocols. The main signs included coughing, sneezing, infraorbital swelling, wasting, and death which were mostly associated with caseous sinusitis. Affected birds had positive samples when stained with anti-Mycoplasma gallisepticum immunohistochemistry and tested by Mycoplasma gallisepticum-Polymerase Chain Reaction. The application of 2 doses of a Mycoplasma gallisepticum vaccine in early 2016 to all the Galliformes in the flock reduced the annual prevalence to 4 clinical cases. Histomoniasis affected and killed 19 out of 27 chukar partridges that were being kept with ring-necked pheasants in the same enclosure. The disease occurred between September and December 2016 and a high prevalence of Heterakis gallinarum was detected in the flock. The main findings included apathy and death linked to hepatic and cecal necrosis. Admixed in the necrotic areas, there were numerous round to oval, eosinophilic, protozoal trophozoites of 15-20 µm in diameter, occasionally containing a 3-5 µm centrally located basophilic nucleus (histomonads) surrounded by a clear halo. Anthelmintic dosing, exchanging and liming the bedding material of the enclosures, and keeping the remaining partridges in an aerial aviary with a wire mesh floor prevented additional cases of histomoniasis. Discussion: In Brazil, as in other countries, the sanitary management practices applied in commercial chicken production reached high levels of technification. However, this is not the case in ornamental bird breeding systems, which may still suffer the impacts of diseases that are practically extinct in industrial chicken flocks. For both diseases, diagnosis was based on typical clinical signs and detection of the pathogens in association with characteristic pathological findings. The occurrence of mycoplasmosis and histomoniasis was associated with improper management practices at the farm; the main risk factors observed were a high turnover of birds, the absence of quarantine, the absence of basic health care, overcrowding and poor hygiene. The prevention of further cases of both diseases was mostly established with the application of basic sanitary measures, including vaccination and anthelmintic dosing, for mycoplasmosis and histomoniasis respectively. This report alerts bird keepers and avian veterinarians of the importance of establishing proper sanitary management in local ornamental bird flocks. Because some of the ornamental bird species that have been commercially propagated worldwide may be included in the list of threatened species, the findings described here also show that simple health care may promote the fight against extinctions.